The professional electronic portfolio project for educational leaders. - Dixon, Robert; Dixon, Kathryn (AARE Inc, 2005)
In November 2004 a group of eleven educational leaders from educational support, secondary and primary schools in Perth, Western Australia, were selected to take place in a trial of an innovative software package designed by the authors, to facilitate the creation of a professional electronic portfolio. A leadership framework developed for the Department of Education and Training, Western Australia (DETWA) with a consortium of academics, (Wildy & Louden 2002) underpins the portfolio. Several competencies and characteristics of school leaders guide the structure of the portfolio. The collection of authentic artefacts to demonstrate these competencies and characteristics and integrate them into the professional electronic portfolio will follow the training phase. Participants were provided with a full day training program during which they were introduced to the conceptual framework underpinning the portfolio and the technology involved to create it. They were provided with a context in which the portfolio could be developed. Each participant was provided with the software package, given an overview and then the opportunity to explore and experiment with the components. They were provided with technological assistance in order to enhance the development of their professional portfolio. This study investigates the training phase of the trial and participant perceptions of how an electronic portfolio promotes professionalism and accountability in educational leadership. It will follow the development of aspirant leaders as they undergo the process of constructing an e-folio over six months, in an effort to understand the efficacy of an electronic portfolio as a medium for demonstrating leadership, for improving leadership and as a mechanism for self-reflection and analysis. It also attempts to bring to light the complexity and multi-faceted issues of school leadership and emergent trends that arise from within the portfolio making process as well as highlighting the effectiveness of information and communication technology (ICT) as a tool for modern leaders. This paper provides an overview of the first stage.